Low density lipoprotein receptor-related protein and apolipoprotein E expression is altered in schizophrenia - Gibbons, Andrew S.; Thomas, Elizabeth A.; Scarr, Elizabeth; Dean, Brian (Frontiers in Psychiatry, 2010)
Our recent microarray study reported altered mRNA expression of several low density lipoprotein receptor-related proteins (LRP) associated with the first 4 years following diagnosis with schizophrenia. Whilst this finding is novel, apolipoprotein E (APOE), which mediates is activity through LRPs, has been reported by several studies to be altered in brains of subjects with schizophrenia. We used qPCR to measure the expression of LRP2, LRP4, LRP6, LRP8, LRP10 and LRP12 mRNA in Brodmann’s area (BA) 46 of the dorsolateral prefrontal cortex in 15 subjects with short duration of illness schizophrenia (SDS) and 15 pair matched controls. We also used Western blotting to measure APOE protein expression in BA46 from these subjects. Amongst the LRPs examined, LRP10 expression was significantly increased (P=0.03) and LRP12 was significantly decreased (P<0.01) in SDS. APOE protein expression was also increased in SDS (P=0.01). No other marker examined in this study was altered with diagnosis. Our data supports a role for distinct members of the LRP family in the pathology of schizophrenia and adds weight to the hypothesis that aberrant apolipoprotein signalling is involved in the early stages of schizophrenia.